أثر الامتثال على الحوكمة الشرعية في المصارف الإسلامية: The Effect of Compliance on Sharia governance in Islamic Banks - Hamd, Nagi; Lubis, Asmuliadi; Mohd Balwi, Mohd Abd Wahab Fatoni (Journal Al-Muqaddimah, 2023)
The research aimed to identify the Effect of compliance on Sharia governance in Islamic banks in Libya and Jordanian. To the objectives of the research, the research model was built on previous studies. And the study population may consist of employees of Islamic banks in Libya, and through the quantitative approach chosen by the researcher,204 respondents' samples were collected. The questionnaire was used as a tool for collecting primary data. The results showed that compliance affect Sharia governance. The research presented some recommendations, the most important of which are: the banks should have standards of Sharia governance, attention to compliance, and the development of an effective management system for compliance.